(3TQM GdeGFI cdeI GdYdhjIs - (3ejKe GdHMQGfj , ceGd GdOjf,J (B681 (3g` s ((3eMeO Hf efUhQ Hf MSjf Hf Ydi GdWGhSj s)
(3ChdgG (B:s
(3CeG HYO adeG cGf Cced GdSYGOGJ hCJegG hCTQa GdOQLGJ hCgegG s
(3BNQgG (B:s
(3hGfbGOhG Ndac Edi HSGW GdcQGeI s
(3HChdg agQSJ Ke UMMgG LeGd GdOjf eMeO Hf GdYQfOS Ke fSNgG dfaSg Ph GdeSGQi eMeO Hf GdTjN WGgQ GdSeGhi SfI (B1362(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B55s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs